2022
DOI: 10.2147/prbm.s370637
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Influence of COVID-19 on Indian Dentists: A Cross-Sectional Survey

Abstract: Introduction: COVID-19 has had a new challenge on dental workers, radically altering clinical and personal management. The crosssectional survey sought to examine and comprehend the influence of COVID-19 on Indian dentistry practitioners. Methods: A 38-item questionnaire-based survey was communicated to Indian dental practitioners through a web-based form (Google form). The questionnaire was categorized into four sections: (i) Personal protective equipment (PPE), (ii) dental treatments, (iii) auxiliary managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Moreover, the societal and cultural norms of advanced nations have undergone significant transformations, aligning with and bolstering the digitalization trend. These shifts include urbanization, centralized systems, increased mobility, and the omnipresence of smartphones and tablets, coupled with the interconnectedness of the Internet of things (IoT), as well as marketplaces driven by efficiency [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the societal and cultural norms of advanced nations have undergone significant transformations, aligning with and bolstering the digitalization trend. These shifts include urbanization, centralized systems, increased mobility, and the omnipresence of smartphones and tablets, coupled with the interconnectedness of the Internet of things (IoT), as well as marketplaces driven by efficiency [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tysiąc-Miśta et al [ 33 ], in a study on Polish dentists, highlighted the negative impact of the pandemic on the economy, as did Shinde et al [ 34 ], who, like the majority of Indian dentists, reported a considerable impact on financial concerns, with both emotional and professional repercussions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 34.2% of dentists reported experiencing their auxiliary staff leaving their clinical practice. 6 Likewise, researchers in China observed that the COVID-19 pandemic significantly influenced the demand for dental services. A retrospective study conducted in Beijing, China, indicated that 1567 patients received emergency dental care pre-COVID-19, in contrast to 970 patients throughout the pandemic.…”
Section: Introductionmentioning
confidence: 99%